Proactive control for conflict resolution is intact in subclinical obsessive-compulsive individuals - Fornaro, Silvia; Visalli, Antonino; Viviani, Giada; Ambrosini, Ettore; Vallesi, Antonino (Frontiers in Psychology, 2024)
Background: Obsessive-compulsive (OC) traits (i.e., tendency to implement stereotyped behaviors to avoid negative consequences) are transversally observed in psychiatric disorders largely differing in terms of clinical manifestations and etiopathogenesis. Interestingly, OC traits were also extensively found in the prodromal phases of the full-blown psychopathology and in healthy relatives of affected individuals. Moreover, OC traits were found to be associated – and possibly underlain by – cognitive control impairments. Nonetheless, the role of such interplay in the onset of OC disorders is yet to be understood. We hypothesized that OC traits are associated with abnormalities in proactively implement cognitive control for solving conflict. Methods: We administered healthy individuals (n = 104) with the perifoveal spatial Stroop task to measure their ability of solving conflict in a proactive fashion, and with Obsessive-Compulsive Inventory (OCI) to stratify population according to the severity of OC traits. Results: Analysis of response times by means of Linear Mixed-effect models revealed that proactive control performance was not associated with and the severity of OC traits. Furthermore, an equivalence test (Two One-Sided Test) revealed that the association between OCI scores and task performance was equivalent to zero. Conclusions: These results suggest that the interplay between OC traits and proactive control abnormalities might not contribute to the development of OC-related disorders. Therefore, the role of other cognitive endophenotypes should be scrutinized for exploiting alternative prevention and intervention strategies.